Transformasi Promosi Tenun melalui Media Digital pada Yayasan Kriya Minangkabau Lintau Buo - Revika Mastanora; Febria Rahim; David Azis; Muhammad Ibrahim Nasution; Rudi Pranata (Politeknik Piksi Ganesha Indonesia, 2026)
The weaving center holds both cultural and economic value, yet its marketing remains limited due to less appealing promotional content and restricted digital access. This community service program applies the Asset-Based Community Development (ABCD) approach to explore local potential, weaving skills, socio-cultural networks, and available digital tools. Together with the artisans, the team developed a digital marketing vision, produced photo and video content, created digital and printed catalogs, conducted social media training, and implemented personal selling simulations. After implementation, the artisans now have active social media accounts, are able to produce aesthetic visual content, and have begun using both digital and printed catalogs. Digital promotion activities have increased, accompanied by a shift in attitude toward technology-based marketing. The combination of ABCD and digital strategies proves effective in strengthening the competitiveness of traditional woven products. For sustainability, improvements in packaging, brand identity, network expansion, and long-term monitoring are needed